Comprehensive Characterization of Ageing-Relevant Subtypes Associated With Different Tumorigenesis and Tumor Microenvironment in Prostate Cancer - Huang, Liang; Xu, Zhenzhou; Xie, Yu; Jiang, Shusuan; Han, Weiqing; Tang, Zhengyan; Zhu, Quan (Frontiers in Molecular Biosciences, 2022)
Objective: Accumulated evidences demonstrate ageing as a robust risk factor of prostate cancer prognosis. Herein, we conducted a systematic analysis about ageing-relevant molecules and relevant tumor microenvironment features in prostate cancer. Methods: Transcriptome data, clinical information and mutational data of prostate cancer patients were retrospectively collected from TCGA cohort. In accordance with the expression of specific ageing-relevant genes, prostate cancer patients were clustered with consensus clustering analyses. WGCNA was adopted for determination of subtype-associated co-expression modules and genes. Thereafter, characteristic genes were further screened with random forest algorithm and a prognostic model was conducted with multivariate cox regression analyses. Tumor microenvironment-infiltrating immune cells were estimated with ssGSEA and ESTIMATE. Activities of cancer immunity cycle and expression of HLA and immune checkpoint molecules were then quantified across prostate cancer. A serious experiments were conducted for investigating the roles of EIF2S2 in prostate tumorigenesis. Results: This study characterized three ageing-relevant subtypes (C1, C2 and C3) with diverse clinical prognosis. Subtype C1 presented the features of low mutational frequency and immune activation; C2 was characterized by stromal and immune activation; and C3 showed immune suppression. An ageing-derived gene signature was conducted, which independently and robustly predicted patients’ prognosis. Additionally, this signature was in relation to immune inactivation. Among the genes in the signature, EIF2S2 triggered proliferation, invasion and migration of LNCaP and PC-3 cells. Conclusion: Collectively, ageing-relevant molecular subtypes and gene signature might be of great significance to determine clinical outcomes and tumor microenvironment features and immunotherapeutic responses in prostate cancer.